Antimicrobial Resistance Profiling and Molecular Epidemiological Analysis of Extended Spectrum β-Lactamases Produced by Extraintestinal Invasive Escherichia coli Isolates From Ethiopia: The Presence of International High-Risk Clones ST131 and ST410 Revealed - Negeri, Abebe Aseffa; Mamo, Hassen; Gurung, Jyoti M.; Firoj Mahmud, A. K. M.; Fällman, Maria; Seyoum, Eyasu Tigabu; Feleke Desta, Adey; Francis, Matthew S. (Frontiers in Microbiology, 2021)
The treatment of Escherichia coli infections is a challenge because of the emergence and rapid spread of multidrug resistant strains. Particular problems are those strains that produce extended spectrum β-lactamases (ESBL’s). Although the global characterization of these enzymes is advanced, knowledge of their molecular basis among clinical E. coli isolates in Ethiopia is extremely limited. This study intends to address this knowledge gap. The study combines antimicrobial resistance profiling and molecular epidemiology of ESBL genes among 204 E .coli clinical isolates collected from patient urine, blood and pus at four geographically distinct health facilities in Ethiopia. All isolates exhibited multidrug resistance, with extensive resistance to ampicillin and first to fourth line generation cephalosporins and sulfamethoxazole-trimethoprim and ciprofloxacin. Extended spectrum β-lactamase genes were detected in 189 strains, and all but one were positive for CTX-Ms β-lactamases. Genes encoding for the group-1 CTX-Ms enzymes were most prolific, and CTX-M-15 was the most common ESBL identified. Group-9 CTX-Ms including CTX-M-14 and CTX-27 were detected only in 12 isolates and SHV ESBL types were identified in just 8 isolates. Bacterial typing revealed a high amount of strains associated with the B2 phylogenetic group. Crucially, the international high risk clones ST131 and ST410 were among the sequence types identified. This first time study revealed a high prevalence of CTX-M type ESBL’s circulating among E. coli clinical isolates in Ethiopia. Critically, they are associated with multidrug resistance phenotypes and high-risk clones first characterized in other parts of the world.